A Preliminary Evaluation of Interactive Video Simulation Training for Campus Law Enforcement in California - Kase, Courtney Ann (RAND Corporation, 2016)
This report evaluates the Interactive Video Simulation Training to help campus law enforcement professionals refer and intervene with college students experiencing psychological distress.